2020
DOI: 10.15191/nwajom.2020.0804
|View full text |Cite
|
Sign up to set email alerts
|

An Exploratory, Preliminary Report on United States Weather Education Trends and General Population Links Between Weather Salience and Systemizing

Abstract: Meteorologists have been interested in STEM (science, technology, engineering, and math) education endeavors for many years. The present study’s authors recently observed an apparent trend in United States public schools away from weather content in physical science classes, especially at higher grade levels. Through the blending of multiple psychological theories, this study sought to examine when people in the United States are presented with educational weather content at the Kindergarten to Grade 12 (K-12)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 53 publications
(49 reference statements)
0
4
0
Order By: Relevance
“…We believe that discerning the viability of this trait will be essential to furthering research into NEED FOR COGNITION ABOUT WEATHER 12 weather salience and its associated curiosities (Bolton et al, 2020;Bolton et al, 2021;Stewart & Bolton, 2021). Furthermore, we see such a construct as enabling a higher-resolution examination of nature connectedness and even potential nature-wellbeing factors.…”
Section: Some Concluding Thoughts On a Need For Cognition About Weathermentioning
confidence: 93%
See 1 more Smart Citation
“…We believe that discerning the viability of this trait will be essential to furthering research into NEED FOR COGNITION ABOUT WEATHER 12 weather salience and its associated curiosities (Bolton et al, 2020;Bolton et al, 2021;Stewart & Bolton, 2021). Furthermore, we see such a construct as enabling a higher-resolution examination of nature connectedness and even potential nature-wellbeing factors.…”
Section: Some Concluding Thoughts On a Need For Cognition About Weathermentioning
confidence: 93%
“…Biophobia, however, is also associated with the inanimate aspects of nature: Orr (1993) suggested that biophillic or biophobic beliefs, feelings, and tendencies arise in early childhood as a result of positive or negative experiences with nature. There is some evidence for this (e.g., Bolton et al, 2020 on weather salience or psychological attention to weather; and Richardson et al, 2019 on nature connection). Kellert (1997) furthered this line of thought by suggesting dispositional nature connectedness is also developmentally influenced by lived experiences of weather, and by socio-cultural influences.…”
Section: Need For Cognition About Weathermentioning
confidence: 99%
“…Scores on the weather salience questionnaire (WxSQ) have correlated positively with perceptual curiosity and the ability to attend to weather-related stimuli in the environment [15,112]; consulting multiple electronic sources for weather information [12]; detailorientation and pattern recognition [113][114][115][116]; trait openness, weather-warning awareness, storm preparation self-efficacy beliefs, and both generalized epistemic curiosity as well as epistemic weather curiosity [116]. Weather salient people thus bring an interest and acuity to the weather and to weather-related information products.…”
Section: Weather Saliencementioning
confidence: 99%
“…Future research may control for this by measuring the intensity and quality of weather interest, since these tend to have a typical distribution (Bolton & Lazarro, 2022). Weather interest starts early in life (Bolton et al, 2020;Bolton & Lazzaro, 2022;DeLoache et al, 2007;Rosen, 2023).…”
Section: Csas Efficient Perceptionmentioning
confidence: 99%